Evaluasi Kesehatan Ekosistem Mangrove Menggunakan Indeks MHI (Mangrove Health Indeks) serta Identifikasi Spesies Dominan di Pesisir Tuban dan Lamongan - Prayogo, Luhur Moekti; Sudianto, Achmad (Universitas Trunojoyo Madura, 2025)
Mangrove ecosystems play a vital role in protecting coastlines, sequestering carbon, and sustaining coastal biodiversity. However, various pressures such as land conversion, abrasion, and human activities are causing degradation in these ecosystems. This study aims to assess the health condition of mangroves in Tuban and Lamongan Regencies through an integrative approach based on Mangrove Health Index (MHI), Normalized Difference Vegetation Index (NDVI) from Sentinel-2A images, and field data. The results of the study showed that the total area of mangroves in the two regions reached 178.88 hectares, with the dominance of medium density (56.47%) and high density (80.37%) which described relatively healthy vegetation conditions. Lamongan Regency recorded higher species diversity (10 types) than Tuban (7 types). The species found include Rhizophora mucronata, R. apiculata, R. stylosa, Avicennia marina, A. officinalis, A. alba, Bruguiera gymnorrhiza, Ceriops tagal, Aegiceras corniculatum, and Sonneratia alba. NDVI analysis showed a positive correlation with MHI, with the eastern Lamongan area and central Tuban as healthy mangrove zones. These findings reinforce the relevance of the use of remote sensing data in coastal ecosystem mapping, but still require field validation for ecological accuracy. This study recommends the integration of spatial approaches with community-based rehabilitation policies to strengthen the sustainability of mangrove management.